The impact of physical exercise on internalizing and externalizing problem behaviors among middle school students: correlation and regression prediction analysis - Jingtao Wu; Xinjuan Zhao; Yanhong Shao; Wanli Zang; Hu Jun; Wenjun Yu (Child and Adolescent Psychiatry and Mental Health)
Abstract Background This study explored the impact of physical exercise on internalizing and externalizing problem behaviors among Chinese middle school students. Methods A cross-sectional survey was conducted among 6368 middle school students from Sichuan, Guangdong, Shandong, Henan, and Jiangxi provinces, using the International Physical Activity Questionnaire (IPAQ), Achenbach Youth Self-Report (YSR), and Depression-Anxiety-Stress Scales (DASS). Latent class analysis, multiple linear regression, and Kendall’s tau coefficient tests were employed to analyze the data. Results Physical exercise significantly reduced externalizing problem behaviors, including impulsivity (β = 0.188, p < 0.001), hostility (β = 0.129, p < 0.001), and aggressiveness (β = 0.158, p < 0.001), and also alleviated depression (β = 0.087, p < 0.01). Latent class analysis revealed that students with high levels of exercise had significantly fewer externalizing behaviors compared to low-level exercisers (p < 0.001). High-intensity exercise had greater effects, particularly on impulsivity and hostility. Rural male students exhibited higher levels of aggressiveness and hostility, while urban female students benefited more from exercise interventions. Conclusion Physical exercise has a significant positive impact on reducing externalizing problem behaviors, especially impulsivity, hostility, and aggressiveness, among middle school students. However, its effects on internalizing behaviors are relatively limited. Intervention strategies should consider individual characteristics such as gender and location to maximize effectiveness.